Mortality of patients undergoing cardiac surgery (Research, Society and Development, 2021)
Objective: To evaluate the mortality of patients after cardiac surgery in a hospital of the southern region. Method: sectional study fulfilled in a database. Participants were patients who underwent cardiac surgery, from July 2015 to July 2019, totaling 62 electronics medical records. The outcome was mortality from any cause during hospitalization with the type of surgery, health history and the profile of the patient. Results: The mortality rate was 9.6%, most of them female, married, retired, with complete elementary school. The chance of death was higher among the elderly. The prevalence of postoperative complications was 25.8%, being more frequent in heart valve surgery. Women were twice as likely to develop complications. The hospitalization time was also 2,6 times longer in those who had complications. Health history was not relevant to any of the outcomes. Conclusions and implications for the practice: Complications increased the length of hospital internment and the mortality rate. Evaluating these factors allows better planning of care by nurses.